ANALISIS KEBIJAKAN PERCEPATAN INVESTASI PADA KAWASAN TERDAMPAK BENCANA LUMPUR SIDOARJO: (Studi Tentang Peraturan Bupati Sidoarjo Nomor 52 Tahun 2020 tentang Pelaksanaan Percepatan Investasi pada Kawasan Terdampak Lumpur Sidoarjo) - Putri Benida (Jurnal Administrasi Publik, 2023)
Analysis of Investment Acceleration Policy in Areas Affected by the Sidoarjo Mud Disaster (Study of Sidoarjo Regent's Regulation Number 52 of 2020 concerning the Implementation of Accelerating Investment in Areas Affected by the Sidoarjo Mudflow). Background Research is Sidoarjo Regent Regulation Number 52 of 2020 despite being implemented, Porong District as one of the districts in the typology zone affected by Lapindo heat mud, has an unfavorable economic condition, when compared to other districts in the same area. Problem Formulation In this study: What is the formulation, implementation and evaluation of investment acceleration policies in the Sidoarjo mud disaster affected area (study of Sidoarjo Regent Regulation Number 52 of 2020 concerning Implementation of Investment Acceleration in Sidoarjo Mud affected areas)? The findings in the field show that the policy formulation (Winarno, 2014), related to the target group and the absence of alternative policies. Implementation of Policy (Grindle, 1980: 11), related to the absence of socialization to investors and entrepreneurs to eliminate the negative stigma of Lapindo Sidoarjo mud which causes fear of entrepreneurs and frequent changes in human resources responsible for the implementation of policies, with the transfer of knowledge that has not been maximized. Policy Evaluation (Dunn, 2003), related to measuring devices/indicators that are clearly stated and standard which are the benchmark of the measurement of policy success.